CLASSIFICATION OF ANTHROPOGENIC IMPACT ON GEOLOGICAL ENVIRONMENT (Oil and Gas Engineering, 2017)
The analysis of anthropogenic factors and proposes an improved generalized classification of anthropogenic impacts on the geological environment. Dedicated effects following classes: physical, physical-chemical, chemical, biological and combined. Class physical effects added by an electric wave and acts on the mountains. Keywords: human impact, geological environment, classification, analysis of anthropogenic factors.